Identifikasi Perlindungan Hukum Terhadap Debitur Atas Pelaksanaan Lelang Berdasarkan Undang-Undang Hak Tanggungan - Lawrina Cristi Natalia Lumare; Gunawan Djajaputra (LPPM Universitas Ekasakti Padang, 2023)
This paper research uses the Normative Juridical research method. Land is the safest object of collateral and has relatively high economic value. The land that is pledged as collateral is then tied up and registered with the local land office to be encumbered with mortgage rights. The consequence of having a mortgage right is that if the debtor breaks his promise, the bank has the authority to auction the collateral object. In order to provide legal protection for the debtor's interests in the auction of mortgage objects, the bank is obliged to carry out the execution in accordance with applicable regulations, one of which is that the auction of mortgage objects must be in accordance with the Mortgage Rights Law in accordance with the market price or in accordance with the limit value, so that does not harm the debtor.